Grotesque and Social Criticism in Two Texts of Prosas bárbaras, by Eça de Queirós - Carniel, Jean Carlos [UNESP]; Pavanelo, Luciene Marie [UNESP] (Masaryk University Press, 2020)
We aim, with this study, to investigate the narratives “Farsas” and “Onfália Benoiton” written by the Portuguese author Eça de Queirós, published in the newspaper Gazeta de Portugal in the 1860s, therefore, at the beginning of the writer’s career, and posthumously collected into Prosas bárbaras, in order to verify how is the presence of the grotesque in both stories. We argue that the unusual is a common feature of Prosas bárbaras and, as we intend to demonstrate, social criticism, a characteristic of the author’s realistic production, is also present in narratives linked to the fantastic.
O grotesco e a crítica social em dois textos de Prosas bárbaras, de Eça de Queirós
Keywords: Eça de Queirós; Grotesque; Social criticism